Tactical actions during opponent throw-ins in soccer in the German Bundesliga - Auguste, C.; Prestel, C. (Journal of Physical Education and Sport, 2021)
Problem statement: Due to the high performance density and the high level of training in professional soccer, every opportunity is used to develop a possibly decisive advantage over the opponent, which underlines the relevance of analyzing tactical means. Purpose: This study aims to analyze team tactical behavior during opponent throw-ins in elite soccer. Approach: A video-based systematic soccer match analysis was conducted with the 18 German Bundesliga teams of the 2019/20 season. A total of 265 throw-ins from 85 five-minute match sequences were analyzed with regard to the zone and direction of the throw-in, the score, the match period, the pressure exerted, and the outcome. Frequency analyses, chi-square tests, ANOVA, and Duncan's post-hoc tests were applied. Results: In our study, the throw-in team remained in possession of the ball in more than half (54.0%) of the throw-ins. Putting higher pressure on the opponent facilitated a greater success rate of recovering the ball for the defending team, Eta² = 57.221, df = 2, p < .001. Trailing teams increased the pressure on the opponent during the throw-in, F(2, 265) = 3.692, p = .026, Eta² = .027; however, this behavior was not reinforced during crunchtime, F(2, 1, 265) = 1.922, p = .148, Eta² = .015. Conclusions: The findings suggest that coaches should consider opposing throw-ins as a trigger for team tactical pressing and highlight the importance of exerting a strong form of disruptive influence on the opponent during throw-ins, as this is an excellent opportunity for recovering the ball.